2020
DOI: 10.1149/1945-7111/ab743f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Annealing Temperature of Ni-P/Si on its Lithiation and Delithiation Properties

Abstract: Annealed Ni–P–coated Si (Ni–P/Si) anodes for lithium-ion batteries have shown a superior cycle life with discharge capacity of 1000 mA h g−1 over 1100 cycles in some ionic-liquid electrolytes. However, the annealing temperature has yet to be optimized for Ni–P/Si electrodes. We investigated the electrochemical performance of Ni–P/Si electrode annealed at various temperatures in this study. The Ni–P/Si electrodes annealed at 800 ± 20 °C exhibited a superior cycle life with a reversible capacity of 1000 mA h g−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…These include reducing the size of the Si particles to prevent generation of stress, , doping Si with impurities, such as boron and phosphorous, to suppress the Si-to-Li 15 Si 4 phase transition, and/or increasing its electrical conductivity, , and preparing lithium silicides to decrease the relative volume change in Si during charge–discharge cycles . Other approaches involve coating Si with conductive materials to lower the electrical resistivity , or synthesizing Si-based alloys to enhance the stability of the electrode structure during cycling. Moreover, film-forming additives or ionic liquid electrolytes have been utilized for the construction of an optimal solid–electrolyte interphase. Lastly, composites have been prepared to improve the mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…These include reducing the size of the Si particles to prevent generation of stress, , doping Si with impurities, such as boron and phosphorous, to suppress the Si-to-Li 15 Si 4 phase transition, and/or increasing its electrical conductivity, , and preparing lithium silicides to decrease the relative volume change in Si during charge–discharge cycles . Other approaches involve coating Si with conductive materials to lower the electrical resistivity , or synthesizing Si-based alloys to enhance the stability of the electrode structure during cycling. Moreover, film-forming additives or ionic liquid electrolytes have been utilized for the construction of an optimal solid–electrolyte interphase. Lastly, composites have been prepared to improve the mechanical properties …”
Section: Introductionmentioning
confidence: 99%
“…6 was obtained after pre-cycling. 47 Thus, the initial discharge capacities in Fig. 6 were close to 1000 mA h g ¹1 .…”
Section: Rate Performance Of Fesi 2 /Si Composite Electrodesmentioning
confidence: 63%
“…We have demonstrated that Si-based electrodes offer greater lithiation/delithiation properties in some ionic-liquid electrolytes compared to that in conventional organicliquid electrolytes in addition to the safety. 8,[41][42][43][44][45][46][47] We have investigated the effect of cation structure of N-methyl-N-propylpyrrolidinium bis(trifluoromethanesulfonyl)amide (TFSA)-based ionicliquid electrolyte on the electrochemical performance of Si-based electrodes. 48 1-((2-methoxyethoxy)methyl)-1-methylpiperidinium (PP1MEM) cation played a role reducing the interaction between Li ion and TFSA anions, and Li + transfer at the electrode-Electrochemistry electrolyte interface in PP1MEM-TFSA was remarkably improved compared with that in 1-hexyl-1-methylpiperidinium (PP16)-TFSA; the introduction of ether functional group into cation is valid to enhance the electrode property.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Precycling was conducted as follows to form a good surface film on the electrode; the Si- or P-doped Si electrode was charged from open circuit voltage (OCV) to 0.500 V vs Li + /Li at 0.1 C , maintained at 0.500 V vs Li + /Li for 12 h, and then discharged to 2.000 V vs Li + /Li at 0.1 C (1 C : 3600 mA g –1 ). 15 That is, the charge and discharge procedures of the precycling were conducted by the constant current (CC) and constant voltage (CV) mode and CC mode, respectively. Charge–discharge testing was performed at various temperatures between 303 and 233 K, whereas low-temperature testing was conducted at 263 K. The charge capacity limit was determined by controlling the limitation time to approximately 17 and 8 min for the 1000 and 500 mA h g –1 capacity limitation, respectively.…”
Section: Methodsmentioning
confidence: 99%